CRITICAL LITERATURE REVIEW IN TEFL RESEARCH: TOWARDS INTERDISCIPLINARY STUDY - Wakhid Nashruddin; Hanna Azmi Zakiyyah Mustaqimah (IAIN Syekh Nurjati Cirebon, 2020)
The fact that English as a second language is perceived to be failed has been a source of criticism for stagnating research in English Language Teaching (ELT). One explanation is that the essence of human learning language has not been taken into account. Furthermore, the tendency that single model of theory applications narrow the subject of research in ELT, using linguistic theories to develop language capacity. Brain study, such as neuroscience, seems to be neglected for considerations that it is irrelevant with language learning. This article identifies possibilities of using a new approach for developing the area of TEFL. As this is literature review, the report is to argue that critical literature review may be useful for initial stage studies, crossing the boundaries of what is called a relevant or irrelevant field, and to identify possible steps in doing critical literature review.